Being Reflective Student Tutors Through Community Service Programs - da Silva, Anna; Junita, Junita; Bryant Tigor Pasaribu, Joseph; Tavian, Yugies; Rohani Manurung, Asima (Politeknik Negeri Jember, 2024)
This article reports the integration of a community service to one course of a master’s program in one private university. Eighteen students were involved in the program that was designed to be part of learning the topics of the course. They had to prepare the syllabus, teach English vocabulary to elementary school students who joined one learning community in East Jakarta under the guidance of the lecturer. In addition to teaching, the students had to create modules on English vocabulary learning, and reflective essays on their teaching and module writing experiences. The aims of the integrated community service to learning program were to provide learning experiences that consist of real application of the English language learning and teaching theories that they have received in the classroom, and reflection upon those experiences. It is expected that the experiences will promote social awareness and contribution to providing free education services to those having limited access to private and profit-making learning centers. The article concludes by highlighting the importance of this model of integration.